The Relation Between College Students’ Social Anxiety and Mobile Phone Addiction: The Mediating Role of Regulatory Emotional Self-Efficacy and Subjective Well-Being - Xiao, Zhenlei; Huang, Jianhao (Frontiers in Psychology, 2022)
The present study explores the underlying mechanism of the relationship between college students’ social anxiety and mobile phone addiction. Adopting college students’ social anxiety scale, regulatory emotional self-efficacy scale, subjective well-being scale and mobile phone addiction scale, this research tested valid samples of 680 Chinese college students. The results indicated that social anxiety exerted a significant and positive impact on mobile phone addiction. Regulatory emotional self-efficacy played a partial mediating role between social anxiety and mobile phone addiction. Subjective well-being also played a partial mediating role between social anxiety and mobile phone addiction. Moreover, both regulatory emotional self-efficacy and subjective well-being were found to play a chain mediating role between social anxiety and mobile phone addiction. The study provides valuable insights into the impact of college students’ social anxiety on mobile phone addiction.